Coaching Jiwa Merdeka sebagai Proses Pembangunan Karakter Guru dalam Rangka Peningkatan Kualitas PAUD di Daerah Istimewa Yogyakarta - Heri Santoso; Hastangka Hastangka; Dela Khoirul Ainia; Kusuma Putri (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of community service Â is to to delivery services forÂ  childhood education teachers through coaching model of â€œIndependent Soulâ€ in the context of character development of PAUD teachers in dealing with the Covid 19 pandemic, and to improve the quality of PAUD. This program uses a qualitative approach. The data in this research were obtained through FGDs, interviews, and literature studies. The activity mentioned in this program Â is an effort to hold a community-service based program to apply the appropriate technology known as Teknologi Tepat Guna (TTG) in education. The result of the activity indicates that the right methods and approaches to raise motivation and enthusiasm for PAUD teachers during the COVID-19 pandemic are coaching and training that emphasizes the aspects of sense and soul processing. Those methods and approaches are proven to give a positive impression for the participants.